Implementation Study of Retention Programs and It’s Impact on Turnover Intention Nurses in Hospital - Lucia Ni Luh Yuniarti; Tutiany Tutiany (Universitas Triatma Mulya, 2019)
Introduction. Nurse turnover will harm the hospital both in terms of costs, resources, and motivation. Turnover can be predicted by exploring the turnover intention of the nurses. Nurses' turnover intention is closely related to the practice of nurse resource management in implementing policies including compensation, career development and work design. The study aims to analyze and identify the effect of retention programs (compensation, career path, work design) on nurses' turnover intention. Methods. The mixed method parallel convergent approach is used in the study. Simple random sampling was taken on 200 respondent nurses in three private hospitals. Semi structure interviews were conducted on 15 participants. Results. Regression test results show that there is a significant effect between compensation retention programs (R = 0.477; p = 0.000; β = 0.23), career development (R = 0.493; p = 0.000; β = 0.22), work design (R = 0.422; p = 0.000, β = 0.16) on nurses' turnover intention. The most dominant factor is compensation (β = 0.265, p = 0.000) compared to career development and work design. The results of qualitative research showed that the key participants stated that compensation was felt not adequate with the nurse profession, the implementation of career development programs had not increased motivation and the workload was felt too much as a result of too many non-nursing tasks. Conclusion. Implications for nursing and hospital management, it is important for nurse managers to have the ability to plan and evaluate policies related to compensation, career development, and work design to improve nurse retention.